P-764 Is children's health up to two years of age affected by embryo vitrification?. (30th June 2022) - Belva, F; Blockeel, C; Roelants, M; Keymolen, K; Buysse, A; Verheyen, G; Tournaye, H; Hes, F; Van Landuyt, L
Abstract: Study question: Does embryo vitrification affect children's health including growth, up to 2 years of age when compared to fresh embryo transfer? Summary answer: While embryo vitrification had an impact on birth parameters, no differences in growth or health outcomes were found up to 2 years of age. What is known already: Vitrification has become the preferred cryopreservation method for embryos. Frozen embryo transfer has been repeatedly associated with altered health outcomes when compared with fresh transfer including a decreased risk for small-for gestational age (SGA) and an increased risk for large-for-gestational-age (LGA) and macrosomia. Not only there is uncertainty which factors are responsible for the observed differences, also the heterogeneity among studies limits overall conclusions. Notwithstanding the observed differences at birth, little is known about growth and health of children born after embryo vitrification beyond birth while aberrant growth trajectories have been linked to cardiometabolic morbidity later in life. Study design, size, duration: This single-center cohort study compared anthropometry and health outcomes in singletons conceived after cleavage-stage or blastocyst-stage embryo vitrification with results after fresh embryo transfer between 2014 and 2018. Pregnancies after PGT, IVM, oocyte vitrification or oocyte/embryo donation were excluded. Eligible singletons living in Belgium and randomly selected for continued follow-up were invited for examination in our center at 2 months (infancy) and 2 years of age (early childhood). Participants/materials, setting, methods: Birth characteristics were available for 1237 and 2063 children born after embryo vitrification and fresh embryo transfer, respectively. Follow-up data were available for 582 and 757 children at 2 months and for 233 and 296 children at 2 years. Growth parameters were adjusted for neonatal, treatment and maternal characteristics. Subgroup analysis according to cycle regimen (HRT versus NC) and strategy (freeze-all versus previous fresh cycle) was performed. In addition, outcomes restricted to blastocysts are presented. Main results and the role of chance: Mothers giving birth to a child conceived after embryo vitrification presented more often with pregnancy-induced hypertensive disorders than controls (P < 0.001). Birthweight, height and head circumference SDS of children born after embryo vitrification were higher than for children born after fresh embryo transfer (all P < 0.001) even after adjustment for neonatal, treatment and maternal characteristics. Embryo vitrification was also associated with a decreased risk of SGA (AOR 0.48; 0.00, 0.44) and an increased risk of macrosomia and LGA (AOR 3.59; 1.12, 11.59)(all P < 0.05). Restricting the sample to blastocysts (n = 1795), we found a higher birthweight SDS and increased risks of LGA, macrosomia and pregnancy-induced hypertensive disorders after vitrification (all P < 0.05). At infancy, weight and height SDS were larger for children born after embryo vitrification, but not after adjustment for co-variates. At childhood, no differences in anthropometrics were found between the groups. Weight and height gain from birth to infancy and from infancy to early childhood were comparable between the groups. Until 2 years, comparable rates of severe developmental problems, hospital admissions, surgical interventions and of chronic medication intake were found between the groups. Subgroup analysis showed that growth parameters at all ages were not affected by cycle regimen or cycle strategy. Limitations, reasons for caution: Participation rate at 2 years was lower than expected in both groups, probably due to cancellation/postponement of the visit related to the corona pandemic. Furthermore, although cycle strategy was not found to affect growth parameters, the sample size of the subgroup analysis remains rather small to draw firm conclusions. Wider implications of the findings: When adjusted for co-variates including birthweight, the observed differences in anthropometrics at birth in children born after embryo vitrification attenuated by 2 years of age. This suggests that outcomes in early childhood are determined by size at birth. Trial registration number: Not applicable